Chemical composition, antimicrobial, and antioxidant properties of essential oils from Artemisia herba-alba asso. and Artemisia huguetii caball. from Morocco: in vitro and in silico evaluation - El Ouardi, Mohamed; Drioiche, Aziz; El Makhoukhi, Fadoua; Mabrouki, Jamal; Hakmi, Mohammed; Al kamaly, Omkulthom; A. Alsfouk, Bshra; Eddamsyry, Brahim; Khamar, Hamid; Zair, Touriya; Alaoui El Belghiti, Mohammed (Frontiers in Chemistry, 2024)
Introduction Morocco is home to a remarkable diversity of flora, including several species from the Artemisia genus. This study aims to thoroughly examine the chemical composition of essential oils derived from Artemisia species and assess their antibacterial and antioxidant properties through in vitro experiments and in silico simulations. Methods Samples of Artemisia herba-alba Asso. were collected from Boulemane and Ifrane in Morocco, while Artemisia huguetii Caball. was sampled from Tata, representing regions of the Central Middle Atlas and Western Anti-Atlas. Essential oils were extracted using hydrodistillation, and their chemical composition was analyzed by gas chromatography-mass spectrometry (GC-MS). Antibacterial and antifungal activities were evaluated, and antioxidant properties were assessed using the DPPH assay. In silico predictions of antibacterial and antioxidant activities were performed using computational models. Results The extraction yields varied depending on the geographical origin, ranging from 1.54% to 2.78%. GC-MS analysis revealed significant differences in the chemical composition of the oils from different Artemisia species and regions, with a notable prevalence of oxygenated monoterpenes. Specifically, the oil from Boulemane was rich in thujone, the oil from Ifrane was predominantly composed of camphor, and the oil from Tata contained both camphor and thujone. The oils exhibited stronger antifungal than antibacterial properties, with Enterobacter cloacae strains showing high sensitivity, with minimum inhibitory concentrations (MIC) of approximately 12.5 mg/mL. The Boulemane oil of A. herba-alba displayed the highest antioxidant activity, effectively inhibiting DPPH at a concentration of 13.501 μg/mL. Discussion The in silico simulations predicted that the primary compounds in these essential oils, such as davanone, eucalyptol, camphor, and thujone, would exhibit potent antibacterial and antioxidant properties. These compounds were found to have favorable ADMET characteristics, including good blood-brain barrier permeability, gastrointestinal absorption, and skin penetration. Molecular docking studies revealed strong interactions between these compounds and key target proteins, such as NADPH-dependent catalase and dihydrofolate reductase. The stability of the protein-ligand complexes was confirmed by molecular dynamics, with davanone showing a significant impact. Overall, this study provides a comprehensive understanding of the biological potential of Artemisia essential oils, highlighting davanone as a promising molecule for medicinal or pharmaceutical applications.